A short-time performance analysis in table tennis - Tamaki, S.; Yoshida, K.; Yamada, K. (International Journal of Table Tennis Sciences, 2013)
A method of table tennis performance analysis is proposed. The key features of the proposed method is (1) the data collecting operation does not require a lot of time nor heavy workload, (2) providing performance indicators for the scoring possibility depends on the shot number. In the analysis, shot number of scoring is collected and used to automate collecting other kinds of data based on the assumption that each player hits the ball alternately. Moreover, shot number of scoring is also used to compute scoring percentage and losing percentage at each shot number. An analysis example verifies the proposed method can be performed in a short time and provide the data for performance analysis in table tennis.